Arabidopsis NITRILASE 1 Contributes to the Regulation of Root Growth and Development through Modulation of Auxin Biosynthesis in Seedlings - Lehmann, Thomas; Janowitz, Tim; Sánchez-Parra, Beatriz; Alonso, Marta-Marina Pérez; Trompetter, Inga; Piotrowski, Markus; Pollmann, Stephan (Frontiers in Plant Science, 2017)
Nitrilases consist of a group of enzymes that catalyze the hydrolysis of organic cyanides. They are found ubiquitously distributed in the plant kingdom. Plant nitrilases are mainly involved in the detoxification of ß-cyanoalanine, a side-product of ethylene biosynthesis. In the model plant Arabidopsis thaliana a second group of Brassicaceae-specific nitrilases (NIT1-3) has been found. This so-called NIT1-subfamily has been associated with the conversion of indole-3-acetonitrile (IAN) into the major plant growth hormone, indole-3-acetic acid (IAA). However, apart of reported functions in defense responses to pathogens and in responses to sulfur depletion, conclusive insight into the general physiological function of the NIT-subfamily nitrilases remains elusive. In this report, we test the both the contribution of the indole-3-acetaldoxime (IAOx) pathway to general auxin biosynthesis and the influence of altered nitrilase expression on plant development. Apart of a comprehensive transcriptomics approach to explore the role of the IAOx route in auxin formation, we took a genetic approach to disclose the function of NITRILASE 1 (NIT1) of A. thaliana. We show that NIT over-expression (NIT1ox) results in seedlings with shorter primary roots, and an increased number of lateral roots. In addition, NIT1ox plants exhibit drastic changes of both free IAA and IAN levels, which are suggested to be the reason for the observed phenotype. On the other hand, NIT2RNAi knockdown lines, capable of suppressing the expression of all members of the NIT1-subfamily, were generated and characterized to substantiate the above-mentioned findings. Our results demonstrate for the first time that Arabidopsis NIT1 has profound effects on root morphogenesis in early seedling development.